Vibrational Cooling After Photo Isomerisation: First Application of a Novel Intramolecular Thermometer. Issue 1 (1999) - Hamm, P.; Ohline, S.; Zurek, M.; Röschinger, T.
Abstract : Femtosecond VIS-pump-IR-probe experiments (time resolution: 300fs, detectable absorption change: 5.10 -5, frequency range: 1000–1800 cm -1 ) were applied to the ultrafast photo isomerisation of azobenzene and the protonated Schiff base of retinal. The energy of the pump photon heats the vibrational system of the molecule, leading to pronounced anharmonic frequency shifts which are dominated by the anharmonic coupling between the investigated high frequency modes to hot low frequency modes. A model taking into account this intramolecular anharmonicity and assuming a well defined intramolecular temperature gives a good fit of the experimental data.